GEOELECTRICAL METHOD FOR SUBSURFACE PROFILING COMPARISON: CASE STUDY IN TAWANG AND SABAK AREA, NORTH KELANTAN, MALAYSIA - Islami, Nur (UI Scholars Hub, 2010)
The study area is located in North Kelantan, Malaysia. The North Kelantan plain is covered with quaternary sediments overlying granite bedrock. The drainage system is dendritic with the main river flowing into the South China Sea. Geoelectrical resistivity profiling surveys were conducted to determine the characteristics of the subsurface and the groundwater within the aquifer. The geoelectric resistivity surveys are made up of twelve resistivity traverses at five different sites. Each site has two or more lines which are perpendicular and parallel to the beach line. The zone of brackish water is very clearly seen in the resistivity inverse model with the position around 20 m of depth. This aquifer is referred to the second aquifer. The subsurface profile in site 1, 2 and 3 which is perpendicular to the beach line shows a wavy pattern. The profile which is parallel to the beach line shows almost planar non wavy pattern. In site 4 and site 5, the profile shows an almost flat.